Insights from expert coaches on technical performance evaluation in rowing: a pilot study - Baumann, Erik; Schmid, Michael J. (Frontiers in Sports and Active Living, 2024)
Introduction Since rowing became an Olympic sport in 1900, rowers have made significant performance gains, partly attributed to increased research, training, and competition knowledge. Rowing technique and biomechanics play an essential role in rowing performance. While some aspects can be quantified with modern tools, coaches' expertise remains essential for technical performance evaluation. Coaches often play a pivotal role in identifying and correcting technical faws; however, novice and intermediate coaches may struggle. This study examines how expert-level rowing coaches assess the technical performance of athletes during on-water rowing. Methods Four current and former national team coaches were interviewed using semi-structured interviews. The repertory grid technique was employed to explore their initial foci when assessing the rowing technique. The acquired data were content-analysed and listed in a summarising table. Results We have detailed both the positive and negative aspects of rowing technique identified by these coaches. Three overarching themes were identified: perceived force application, perceived movement precision, and perceived rhythm and timing. Discussion Examining the categories revealed that the coaches with a shared federation background exhibited a relatively high level of similarity in their initial foci. However, looking into their subjective aspects revealed considerable differences. This leads to the hypothesis that a broad spectrum of unique coaches' criteria can lead to the same or similar technique executions from their athletes.